Coinfection With SARS-CoV-2 and Dengue Virus: A Case Report Highlighting Diagnostic Challenges - Hariadi, Prasetyo; Lokida, Dewi; Menur Naysilla, Adhella; Lukman, Nurhayati; Kosasih, Herman; Mardian, Yan; Andru, Gestana; Pertiwi, Inggar; Sugiyono, Retna I.; Pradana, Antonius A.; Salim, Gustiani; Butar-butar, Deni P.; et al. (Frontiers in Tropical Diseases, 2022)
Background Since its emergence in China, SARS-CoV-2 has infected more than 240 million people worldwide, including in regions where dengue virus (DENV) is hyperendemic such as Latin America and Southeast Asia, including Indonesia. Diagnosis of COVID-19 in dengue endemic regions as well as DENV and SARS-CoV-2 co-infection can be challenging. Case Presentation We describe a 68-year-old woman with diabetes mellitus type II who was admitted to the Tangerang District Hospital on 14 April 2020. She lived in a neighborhood where a few people were contracting dengue fever. She presented with five days of fever, malaise, anorexia, nausea, myalgia, and arthralgia. Hematology revealed anemia, thrombocytopenia, normal leukocyte count, increased neutrophil proportion, and decreased lymphocyte proportion and absolute lymphocytes. Her chest X-ray showed right pericardial infiltrates. Although dengue was clinically suspected, she was also tested for SARS-CoV-2 infection as she met screening criteria. After being confirmed SARS-CoV-2 positive by RT-PCR, she was treated with ceftriaxone, paracetamol, azithromycin, oseltamivir, and chloroquine. She was clinically improved four days later and discharged from the hospital on 25 April 2020 after SARS-CoV-2 RT-PCR was negative on two consecutive samples. Dengue was diagnosed retrospectively based on sero-conversion of dengue IgM and a very high dengue IgG index (ELISA, Focus Diagnostics®, Cypress, CA, USA), and sero-conversion of dengue IgM and positive IgG (Rapid test, PanBio ®Dengue duo cassette, Inverness Medical Innovations, QLD, AU), which was equivalent to high Hemagglutination Inhibition (HI) antibody titer (≥1280) found in secondary dengue infection. Conclusion The overlapping clinical presentations of COVID-19 and dengue; limited diagnostic capacity of laboratories in resource constrained settings; and complexities of interpreting results make identification of COVID-19 in the dengue endemic setting challenging. Clinicians in endemic areas must be aware of diagnostic challenges and maintain a high index of suspicion for COVID-19 coinfection with DENV and other tropical pathogens.